Differences of clinical features, prognosis and genetic mutations in Chinese patients with malignant melanoma and additional primary tumours - Lin, Jing; Lin, Zhongqiao; Chen, Yanping; Wang, Xuefeng; Huang, Yufang; Zhang, Huishan; Zhu, Li; Xu, Zelong; Gao, Xuan; Zhang, Yingqian; Lan, Bin; Chen, Yu (Annals of medicine (Helsinki), 2025)
The differences in the clinical features, prognosis and genetic mutations in Chinese patients with malignant melanoma (MM) and additional primary tumours remain unclear. A retrospective analysis was conducted on patients with malignancies in Fujian Cancer Hospital from January 2007 to September 2022, end follow-up in September 2023. Clinical data were gathered, survival analysis was performed, and genetic mutations were detected. There were 58 of 1223 melanoma patients with melanoma and additional primary tumours, an incidence of 4.74%. Acral MM was the most common subtype (26/58), 23 (39.66%) patients had concomitant digestive tumours. Patients who had MM as their first primary tumour (MMFP) had shorter tumour occurrence intervals (9.93 vs. 57.78 months, = .008) but longer melanoma survival (MM-OS) than the non-MMFP group (100.43 vs. 18.93 months, = .015). Patients with cancer family histories were more likely to have pathogenic and likely pathogenic (P/LP) mutations (2/5 vs. 4/25). The somatic BRAF gene mutation was frequently observed in MM tissue (8/19, 42.11%). Three patients had whole-genome doubling and microsatellite instability-high (MSI-H). The COSMIC2 signature 3 was significantly higher in the P/LP group. The frequency of MM and additional primary tumours is about 5% in Chinese populations. Patients with melanoma diagnosed first have longer melanoma survival. Digestive system tumours were the most concomitant; a digestive examination is advisable, especially for those with an expected overall survival (OS) greater than 10 months. Meanwhile, patient's family cancer history should be followed up in detail, along with completion of germline P/LP mutation and somatic mutation testing, all of which may provide valuable support for further treatment.